Use of recyclable materials in school gardens - Leal, Marisa Menezes (2020)
The use of recyclable materials is an alternative for the preparation of school gardens and for the teaching of environmental education. In addition to being a facilitating tool for learning, the garden, when combined with the themes of environmental education, becomes fundamental for the formation of citizens aware that natural resources can be degraded or depleted. Thus, this study aimed to implement gardens with the use of recyclable material. The vegetable gardens were implemented in The Importance of Planning of Garden at School child education, elementary and high schools. The schools involved were Escola Municipal de Educação Infantil Sol Criança (Santiago-Rio Grande do Sul), Escola Estadual de Ensino Fundamental Bairro Carvalho (Cachoeira do Sul- Rio Grande do Sul), Colégio Estadual Cerro Branco (Cerro Branco- Rio Grande do Sul) e Colégio Totem (Cachoeira do Sul- Rio Grande do Sul). The recyclable materials used to prepare beds and support plants were pet bottles, tires, pallets and shingles. The activities were carried out by the members of the Living Garden Extension Project at School, together with the students and teachers of the schools. The garden space was used as an environment for teaching different subjects and allowed the development of playful and pleasurable activities.